MoS2 graphene fiber based gas sensing devices. (December 2015) - Niu, Yue; Wang, Rongguo; Jiao, Weicheng; Ding, Guomin; Hao, Lifeng; Yang, Fan; He, Xiaodong
Abstract: A facile method is developed to synthesize a fiber-like reduced graphene oxided (rGO)/molybdenum disulfide (MoS2 ) composites through a wet-spinning and a hydrothermal method. In the presence of Dodecyl dimethyl benzyl ammonium chloride, graphene provides a substrate for nucleation of MoS2 . In this composite, MoS2 nanosheets can be anchored onto the surface of graphene through both physical adsorption and electron transfer by hydrothermal method. This process inhibits both graphene and MoS2 layers from stacking together. The gas sensing properties are evaluated in an intelligent gas sensing analysis system. It is demonstrated that the obtained composite fiber devices show an excellent sensitivity and selectivity to NO2 and NH3 than the individual components in different light illumination conditions and the proper proportion of components was detected.